2013
DOI: 10.1016/j.scr.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and immunophenotypic plasticity of malignant cells in human liposarcomas

Abstract: Liposarcomas are tumors arising in white adipose tissue (WAT) with avidity for local recurrence. Aggressive dedifferentiated liposarcomas (DDLS) may arise from well-differentiated subtypes (WDLS) upon disease progression, however, this key issue is unresolved due in large part to knowledge gaps about liposarcoma cellular composition. Here, we wished to improve insights into liposarcoma cellular hierarchy. Tumor section analysis indicated that the populations, distinguishable based on expression of CD34 (a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The ER signaling pathways are implicated in disease progression ( 1 , 26 , 28 , 30 , 36 , 37 ), because the ER status of bone metastases usually correlates with the ER status of the primary tumor ( 28 , 36 ). Relatively little is known about the ER signaling pathways that lead to downstream activation of cellular targets that trigger disease progression; however, a protective role is generally suggested from limited clinical evidence: (1) Rabbani, et al demonstrated a decrease in breast cancer cell growth and parathyroid hormone-related protein (PTHrP) production in response to estradiol ( 38 ); (2) in addition, overexpression of ER decreased tumor growth and reduced bone metastasis formation ( 38 ); (3) other studies have shown that kinase inhibitors that were designed to attenuate a host of pathways activated in breast cancer cells are not able to halt disease spread once multiple osseous metastases have appeared ( 16 , 18 , 28 , 36 , 39 ); and (4) a protective role of ERβ in the progression of breast cancer has been suggested, as higher levels of ERβ are predictive of positive response to the ER modulator tamoxifen ( 40 , 41 ). The role of ERβ both in the primary tumor and in bone marrow where metastases occur has only recently become the focus for the development of treatments in addition to those that target ERα ( 40 42 ), but may provide an important second index by which to stratify risk in patients with ER positive breast cancers.…”
Section: Literature Analysismentioning
confidence: 99%
“…The ER signaling pathways are implicated in disease progression ( 1 , 26 , 28 , 30 , 36 , 37 ), because the ER status of bone metastases usually correlates with the ER status of the primary tumor ( 28 , 36 ). Relatively little is known about the ER signaling pathways that lead to downstream activation of cellular targets that trigger disease progression; however, a protective role is generally suggested from limited clinical evidence: (1) Rabbani, et al demonstrated a decrease in breast cancer cell growth and parathyroid hormone-related protein (PTHrP) production in response to estradiol ( 38 ); (2) in addition, overexpression of ER decreased tumor growth and reduced bone metastasis formation ( 38 ); (3) other studies have shown that kinase inhibitors that were designed to attenuate a host of pathways activated in breast cancer cells are not able to halt disease spread once multiple osseous metastases have appeared ( 16 , 18 , 28 , 36 , 39 ); and (4) a protective role of ERβ in the progression of breast cancer has been suggested, as higher levels of ERβ are predictive of positive response to the ER modulator tamoxifen ( 40 , 41 ). The role of ERβ both in the primary tumor and in bone marrow where metastases occur has only recently become the focus for the development of treatments in addition to those that target ERα ( 40 42 ), but may provide an important second index by which to stratify risk in patients with ER positive breast cancers.…”
Section: Literature Analysismentioning
confidence: 99%
“…There is no evidence that ASCs, or MSCs in general, are directly tumorigenic, although liposarcomas contain an aggressive multipotent malignant population resembling ASCs ( Zhang et al , 2013 ). However, a body of data indicates that these cells may acquire a tumour-supporting function.…”
Section: The Role Of Wat Cells In Cancer Local and Metastatic Cancermentioning
confidence: 99%
“…In xenograft mouse models, both Smith et al and Peng et al have independently confirmed that DD but not WD tumors have the potential to engraft successfully ( 22 , 24 ). As a likely explanation, the highest percentage of CD34-positive stem cells is seen in DD tumors compared to WD and normal fat ( 25 ).…”
Section: Cancer Progenitor Cells In Wd/dd Liposarcomamentioning
confidence: 99%